2010
DOI: 10.1002/jcp.22249
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin down‐regulates the TGF‐β‐mediated synthesis of collagen and fibronectin by human proximal tubule epithelial cells through the EPCR‐dependent activation of PAR‐1

Abstract: Human proximal tubule (HK-2) cells are commonly used as cellular models to understand the mechanism by which inflammatory mediators cause renal injury. It has been observed that thrombin stimulates the expression of TGF-β, extracellular matrix (ECM) proteins and proinflammatory cytokines by HK-2 cells. These in vitro responses correlate well with the pathology of glomerular and tubular diseases observed in acute renal injury. HK-2 cells express PAR-1 and the thrombin activation of this receptor has been report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 49 publications
1
26
0
3
Order By: Relevance
“…26,30,32 The cytoprotective effects of thrombin have also been reported in nonendothelial cells. Thrombin reduces TGF-␤-mediated expression of extracellular matrix proteins in renal tubular cells 28 and thrombin dose dependently regulates proliferation of rat glioma cells. 33 The beneficial effects of low-dose thrombin in endothelial cells and podocytes establish that thrombin can mediate cytoprotection in both cell types constituting the glomerular filtration barrier (endothelial cells and podocytes).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26,30,32 The cytoprotective effects of thrombin have also been reported in nonendothelial cells. Thrombin reduces TGF-␤-mediated expression of extracellular matrix proteins in renal tubular cells 28 and thrombin dose dependently regulates proliferation of rat glioma cells. 33 The beneficial effects of low-dose thrombin in endothelial cells and podocytes establish that thrombin can mediate cytoprotection in both cell types constituting the glomerular filtration barrier (endothelial cells and podocytes).…”
Section: Discussionmentioning
confidence: 99%
“…27 However, recent studies have established that thrombin can mediate cytoprotective effects in endothelial cells in vitro, suggesting that the hemostatic system has a dual function. 26,28 Such a dual function resembles the 2-faced character of reactive oxygen species, also referred to as "redox homeostasis." 29 Given the current and previous results, we propose that the coagulation system has a similar dual function in regulating cellular homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Glucose-induced TGF-β1 mediated increases in ECM have been reported in cultured mesangial cells [24], podocytes [25] and tubular epithelial cells [26], the cumulative effect of which is destruction of the renal parenchyma. A recent study by Reiniger et al (2010) demonstrated that removal of the AGE receptor in the diabetic OVE26 mouse, attenuated the degree of glomerulosclerosis with a concomitant improvement in renal function [27], whilst over-expression of PKC, has been shown to exert fibrotic effects in human proximal tubular cells [28].…”
mentioning
confidence: 90%
“…In secondary hemostasis, thrombin converts fibrinogen into fibrin monomers, finally forming a stable clot that stops bleeding at sites of vascular injury. In addition, thrombin attenuates its own generation through formation of a complex with the endothelial cell (EC) surface receptor thrombomodulin (TM), thereby activating protein C to activated protein C (APC), the main inactivator of activated factor V and activated FVIII [1].…”
Section: Introductionmentioning
confidence: 99%